Molecular tools for controlling nanoparticle size/morphologies - Sahu, P.; Shimpi, J.; Prasad, B.L.V. (Molecular materials: preparation, characterization, and applications, 2017)
The preparation of nanoparticles (especially those of noble metals) predates the coinage of the term nano itself by several centuries. The earliest example of the preparation of nanoparticles has been linked to Roman artisans who created colored glass by probably mixing gold chloride and other salts of noble metals while making glass. Many artistic marvels such as the Lycurgus cup and the glass panels in many European cathedrals were created by this simple procedure. Furthermore, many believe that medicinal preparation such as “aurum potabile” and formulations injected for treating rheumatic arthritis were made of colloidal gold. Several people such as the fourteenth-century Bolognese painters, the alchemists Paracelsus, Andreus Cassius, and Johannes Kunckel are all believed to have made the colloidal form of gold, which is the most studied form among the metallic nanoparticles. However, none of these methods of preparations or people were really interested to see in what form the metals existed in composite/solution or whether these existed 190as small (“nano”) particles. Actually, it was Michael Faraday who first conjectured that the ruby red color imparted to the glass/ceramics could be due to the reduction of gold salts to metallic state. 1 He in fact prepared a “sol” of gold by reacting a gold chloride solution with red phosphorous, thus causing the reduction of gold (III) ions to metallic gold. He was also the first person who inferred that the color imparted to the glass/ceramics could be due to the existence of gold in a “finely divided metallic state.” Several systematic studies by Richard Adolf Zsigmondy, Theodor Svedberg, and Gustav Mie 2-5 on gold nanoparticles followed. However, the preparations in all these studies have been mainly curiosity driven and practical applications, if any, have been rather limited. One of the causes for this limitation could be related to the difficult preparative procedures. This major hurdle has been crossed thanks to the pioneering works first by Turkevich et al. 6 and later by Frens 7, 8 that provided the first major breakthrough as far as the simplification of gold colloid preparation was concerned. Procedures developed by these people were also the first ones where an organic molecule, trisodium citrate, was used for nanoparticle synthesis